A new fully covered metal stent with anti-migration features for the treatment of malignant dysphagia - Walter, Daisy; van den Berg, Maarten W.; van Hooft, Jeanin E.; Boot, Henk; Scheffer, Robert C. H.; Vleggaar, Frank P.; Siersema, Peter D. (Endoscopy, 2014)
Background and study aims: A new esophageal stent with two anti-migration features was developed to minimize migration. The aim of this study was to evaluate the clinical efficacy and safety of this stent in patients with malignant dysphagia. Patients and methods: A total of 40 patients with dysphagia due to a malignant obstruction of the esophagus were prospectively enrolled in this cohort study. Results: Stent placement was technically successful in 39 patients (98 %). The median dysphagia-free time after stent placement was 220 days (95 % confidence interval 94 – 345 days). Nine patients (23 %) experienced recurrent dysphagia due to tissue overgrowth (n = 2), stent fracture (n = 1), and partial (n = 5) or complete (n = 1) stent migration. A total of 16 serious adverse events occurred in 14 patients (36 %), with hemorrhage (n = 3) and severe nausea or vomiting (n = 3) being the most common causes. Conclusions: This new stent design was effective for the palliation of malignant dysphagia and had a low rate of recurrent dysphagia. However, despite the anti-migration features, stent migration was still a major cause of recurrent dysphagia. Furthermore, treatment was associated with a high adverse event rate. Dutch Trial Registration (NTR 3313)